2014
DOI: 10.1038/bjc.2014.346
|View full text |Cite
|
Sign up to set email alerts
|

First-line bevacizumab and capecitabine–oxaliplatin in elderly patients with mCRC: GEMCAD phase II BECOX study

Abstract: Background:Subgroup analyses of clinical studies suggest that bevacizumab plus XELOX is effective and tolerable in elderly patients with metastatic colorectal cancer (mCRC). The prospective BECOX study examined the efficacy and safety of bevacizumab plus XELOX, followed by bevacizumab plus capecitabine in elderly patients with mCRC.Methods:Patients aged ⩾70 years with Eastern Cooperative Oncology Group performance status 0 out of 1 and confirmed mCRC were included. Patients received bevacizumab 7.5 mg kg−1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 46 publications
4
48
0
Order By: Relevance
“…Our findings indicate that the SOx regimen is well tolerated even in older patients with a low rate of clinical adverse events similar to what would be expected with other fluoropyrimidine-oxaliplatin-based combinations, albeit with a much lower rate of HFS [20]. The rate of hematological adverse events also appears to be lower with SOx compared with other fluoropyrimidine-oxaliplatin combinations.…”
Section: Discussionsupporting
confidence: 77%
“…Our findings indicate that the SOx regimen is well tolerated even in older patients with a low rate of clinical adverse events similar to what would be expected with other fluoropyrimidine-oxaliplatin-based combinations, albeit with a much lower rate of HFS [20]. The rate of hematological adverse events also appears to be lower with SOx compared with other fluoropyrimidine-oxaliplatin combinations.…”
Section: Discussionsupporting
confidence: 77%
“…The main inclusion criteria were previously published. 13 Briefly, they were the following: elderly patients (≥70 years old), performance status of 0 or 1, histologically confirmed diagnosis of mCRC not suitable for resection, measurable disease according to RECIST version 1.1, not prior systemic therapy for metastatic disease, and prior adjuvant chemotherapy ended >12 months before starting the study. Exclusion criteria included brain metastases, clinically significant cardiac disease, clinical use of full-dose anticoagulants, and major surgical procedures within 28 days before study entry.…”
Section: Study Populationmentioning
confidence: 99%
“…The BECOX trial was designed to investigate the efficacy and safety of a bevacizumab plus XELOX regimen as a first-line treatment in elderly population diagnosed of mCRC. 13 …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] The studies reviewed reported nausea from 1% to 59% and vomiting from 3% to 32%, with grade 3 or 4 nausea in 1% to 2% of patients and grade 3 or 4 vomiting in 3% to 7%. [1][2][3][4] Prophylactic antiemetic therapy with a steroid and serotonin antagonist is recommended. [13][14][15][16] One group suggests addition of a neurokinin (NK 1 ) antagonist may be appropriate in some patients.…”
Section: A Acute and Delayed Emesis Prophylaxismentioning
confidence: 99%
“…For regimens with an incidence of febrile neutropenia less than 10%, routine prophylactic use of CSFs is not recommended. 26,27 Because febrile neutropenia was reported in 1% to 2% of patients and grade 3 or 4 neutropenia was reported in 4% to 22% of patients in the trials reviewed, [1][2][3][4] primary prophylactic use of CSFs is not recommended. [1][2][3][4] CSFs should be considered if a patient experiences febrile neutropenia or grade 4 neutropenia in a prior cycle of BCapOx.…”
Section: Hematopoietic Growth Factors: Accepted Practicementioning
confidence: 99%